Alternatives to Antibiotics in Semen Extenders: A Review - Morrell, Jane M. (Pathogens, 2014)
Antibiotics are added to semen extenders to be used for artificial insemination (AI) in livestock breeding to control bacterial contamination in semen arising during collection and processing. The antibiotics to be added and their concentrations for semen for international trade are specified by government directives. Since the animal production industry uses large quantities of semen for artificial insemination, large amounts of antibiotics are currently used in semen extenders. Possible alternatives to antibiotics are discussed, including physical removal of the bacteria during semen processing, as well as the development of novel antimicrobials. Colloid centrifugation, particularly Single Layer Centrifugation, when carried out with a strict aseptic technique, offers a feasible method for reducing bacterial contamination in semen and is a practical method for semen processing laboratories to adopt. However, none of these alternatives to antibiotics should replace strict attention to hygiene during semen collection and handling.